Composite heterogeneous nano material as well as preparation method and application thereof

By using In-MOFs precursors to prepare In2S3–xSex@NC composite heterogeneous nanomaterials with anionic defects and uniform heterointerfaces in dopamine electrochemical sensing materials, the problems of poor conductivity and uneven heterointerfaces are solved, and high sensitivity and selectivity dopamine detection is achieved.

CN119774557APending Publication Date: 2025-04-08YANGTZE NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991961.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the development of high sensitivity and selectivity dopamine (DA) electrochemical sensing materials, the prior art has problems of poor conductivity and uneven heterogeneous interfaces, which affects the charge and energy density of the material, resulting in low ion/electron transfer efficiency and insufficient detection stability.

Method used

By using In-MOFs as a precursor, a composite heterogeneous nanomaterial with anionic defects and a uniform heterointerface is constructed, and the S element in In2S3 is partially replaced by Se element, anionic defects are created, and a uniform heterointerface is formed between the polydopamine-derived nitrogen-doped carbon layer and In2S3–xSex.

Benefits of technology

It achieves high sensitivity, low detection limit, excellent anti-interference performance, good stability, repeatability and regeneration, and improves the accuracy and reliability of dopamine detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774557A_ABST
    Figure CN119774557A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrochemical sensing materials, and discloses a composite heterogeneous nano-material and a preparation method and application thereof.The nano-material has rich ion defects and a uniform heterogeneous interface, the anion defects are created by introducing Se element into In2S3 and partially replacing S element with the Se element, and the nano-material has good electrochemical sensing performance. A uniform heterogeneous interface exists between a nitrogen-doped carbon layer derived from polydopamine and In < 2 > S < 3-x > Se < x >, and an adopted precursor is In-MOFs. The In2S3-xSex-atNC composite nanomaterial disclosed by the invention has excellent electro-catalytic properties on dopamine (DA) active molecules, including good selectivity, high sensitivity, low detection limit and good stability and repeatability, and shows a wide application prospect in actual biological sample detection. The In2S3-xSex-coated NC composite nanomaterial disclosed by the invention is low in cost, simple in preparation process, low in energy consumption, very easy in realization of reaction conditions and capable of realizing batch production, and general applicability and practical application potential of a p-region metal compound in biomolecule detection are developed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical sensing materials, and in particular to a composite heterogeneous nanomaterial and a preparation method and application thereof. Background Art

[0002] Dopamine, abbreviated as DA, is an endogenous nitrogen-containing organic compound, also known as catecholethylamine or hydroxytyramine, with a chemical formula of C 8 H 11 NO 2 . In the human body, dopamine, as a major neurotransmitter, plays a vital role in the central nervous system and has an important impact on multiple physiological functions, including the central nervous system, cardiovascular system, endocrine system and renal system. Its abnormal level changes are closely related to various diseases, so it is necessary to quickly and accurately determine the concentration of dopamine in organisms and biological fluids. In order to successfully achieve high sensitivity and superior selectivity for DA analysis, a variety of sensing platforms based on fluorescence, colorimetry, Raman scattering, field effect and electrochemistry have been constructed in the prior art. In contrast, electrochemical sensing technology is favored for its effectiveness and breadth, as well as its ability to analyze the complex mechanisms of DA-related diseases and develop new treatment strategies.

[0003] Although the development of high-performance DA electrochemical sensors largely relies on the strong ability of the sensor matrix to distinguish target signals from coexisting biomolecules, exploring active sensing materials (such as carbon materials, metals and their alloys, metal compounds, etc.) with high sensitivity and selectivity remains a critical and challenging task. Currently, many studies focus on the novel morphology of nanomaterials, while ignoring the optimization of their actual sensing performance. Therefore, it is particularly urgent to adopt specific strategies to develop active sensing materials that can effectively monitor DA.

[0004] Metal chalcogenides (such as sulfides, selenides, etc.) have become a class of electrocatalysts that have attracted much attention due to their diverse chemical valence states, favorable band gaps, high theoretical capacities, and good redox reversibility. These properties enable them to exhibit excellent adsorption and reactivity toward target analytes, thus meeting the requirements of high-performance electrocatalysts. However, current research has mainly focused on d-block transition metal sulfides, which typically contain partially filled d-bands around the Fermi level. In contrast, p-block metals (such as indium, tin, etc.) have less discussed compounds (including chalcogenides) due to their closed d-band shells and lower surface catalytic reactivity. Nevertheless, some p-block metal sulfides, such as the typical indium sulfide (In 2 S 3), due to their high electron affinity, excellent chemical stability, low toxicity and tunable electrical and optical properties, they have gradually attracted widespread attention and are regarded as ideal photoactive materials. In order to further expand the application of p-block metal sulfides, their local environment can be directionally adjusted through specific strategies to activate s / p electrons, thereby developing promising electrocatalysts for sensing. However, the research on p-block metal sulfides in electrocatalytic bioactive molecules is still limited, which motivates us to establish effective principles to optimize the active sites of these materials and expand their application range.

[0005] Vacancy technology—the introduction of defects by doping or substitution—is an effective way to tune the intrinsic electronic properties of host materials, such as structure, mobility, and carrier concentration. This approach can generate additional active sites at the atomic-level interface, thereby significantly enhancing the electrocatalytic performance. In particular, Se, due to its large atomic radius and low electronegativity, as well as its stronger shielding effect on the nuclear charge, when introduced into metal sulfides as a dopant, can not only improve the conductivity by forming widened Se-S interlayer ligands and anion vacancies, but also promote stable electroreaction kinetics by reducing the bond dissociation energy. Despite this, a major problem that metal chalcogenides generally have is poor electrical conductivity. To address this problem, these compounds are usually coupled with carbonaceous materials. However, this combination may also bring new challenges: the heterogeneous interface between polar metal chalcogenides and non-polar carbon matrices may be unevenly distributed, affecting the charge and energy density of the active material, which in turn leads to low ion / electron transfer efficiency and insufficient detection stability. Summary of the invention

[0006] The present invention is intended to provide a composite heterogeneous nanomaterial and a preparation method and application thereof, aiming to develop an active sensing material that can effectively monitor DA, while ensuring that the active sensing material has high sensitivity, low detection limit, excellent anti-interference performance, good stability, repeatability and reproducibility.

[0007] To achieve the above object, the present invention adopts the following technical scheme: a composite heterogeneous nanomaterial, the nanomaterial uses In-MOFs as a precursor, constructs anion defects and a uniform heterogeneous interface, the anion defects are partially replaced by Se elements 2 S 3 The S element in the carbon layer is used to create a uniform heterogeneous interface between the polydopamine-derived nitrogen-doped carbon layer and the In 2 S 3–x Se x between.

[0008] Preferably, as an improvement, the morphology of the In-MOFs precursor is spindle-shaped, flake-shaped or rod-shaped.

[0009] Preferably, as an improvement, the method for preparing the In-MOFs spindle morphology comprises the following steps:

[0010] S1. dissolving a precursor containing an indium source in N,N-dimethylformamide and stirring continuously;

[0011] S2, adding 1,4-phthalic acid and 1,2-benzisothiazolin-3-one to the above solution in sequence, and stirring to mix evenly;

[0012] S3, transferring the mixture into an autoclave, heating and reacting to obtain a white precipitate;

[0013] S4. The white precipitate was centrifuged, washed with DMF and deionized water for multiple times, and freeze-dried to obtain white spindle-shaped In-MOFs.

[0014] Preferably, as an improvement, the method for preparing In-MOFs flake morphology comprises the following steps:

[0015] S1, adding a precursor containing an indium source and 1,3,5-benzenetricarboxylic acid to a mixed solution of N,N-dimethylformamide and a methanol solution;

[0016] S2. After the powder is dissolved, the transparent mixture is transferred to a high-pressure reactor, sealed and heated for reaction;

[0017] S3. The obtained precipitate was centrifuged and washed with methanol several times, and then vacuum dried overnight to obtain white flaky In-MOFs.

[0018] Preferably, as an improvement, the method for preparing In-MOFs rod-like morphology comprises the following steps:

[0019] S1, adding a precursor containing an indium source and 1,4-benzenedicarboxylic acid to N,N-dimethylformamide, and then adding a sodium acetate aqueous solution under vigorous stirring;

[0020] S2, placing the obtained reaction mixture in an oil bath for reaction to obtain a precipitate;

[0021] S3. The obtained precipitate was centrifuged, washed with distilled water and anhydrous ethanol several times, and then vacuum dried to obtain white rod-shaped In-MOFs.

[0022] Preferably, as an improvement, the precursor of the indium source is hydrated indium nitrate (In(NO 3 ) 3 ·4H 2 O、In(NO 3 ) 3 ·5H 2 O、In(NO 3 )3 6H 2 O) at least one.

[0023] Preferably, as an improvement, a method for preparing a composite heterogeneous nanomaterial comprises the following steps:

[0024] Step 1: Add dopamine and In-MOFs powder into a buffer solution and stir at room temperature. When the white In-MOFs turns black, the self-polymerization process is completed. Then filter and wash to obtain the In-MOFs@PDA intermediate.

[0025] Step 2: Place In-MOFs@PDA and sulfur powder in a porcelain boat and perform high-temperature carbonization and sulfurization treatment in a protective atmosphere. After the reaction is completed, cool down to obtain a black sample In 2 S 3 @NC;

[0026] Step 3: In 2 S 3 @NC and tin powder are placed at both ends of a porcelain boat and subjected to high-temperature selenization treatment in a protective atmosphere. After the reaction is completed, the temperature is cooled to obtain the final product In 2 S 3–x Se x @NC.

[0027] Preferably, as an improvement, in step 1, the mass ratio of dopamine to In-MOFs powder is 1:1 to 1:4, the buffer solution is Tris solution, the concentration of the buffer solution is 5 to 20 mM, and the stirring time is 6 to 14 h.

[0028] Preferably, as an improvement, in step 2, the mass ratio of In-MOFs@PDA to sulfur powder is 1:2 to 1:10, and the high temperature carbonization and sulfurization reaction is heated to 400 to 800°C at a heating rate of 1 to 10°C / min, and the reaction time is 1 to 5h; in step 3, In 2 S 3 The mass ratio of @NC to tin powder is 1:1 to 1:4, and the high-temperature selenization reaction is heated to 300 to 700°C at a heating rate of 1 to 10°C / min, and the reaction time is 1 to 5 hours.

[0029] Preferably, as an improvement, a composite heterogeneous nanomaterial is used in detecting dopamine molecules.

[0030] The principle and advantages of this solution are: This technical solution aims at the problems existing in the process of preparing active sensing materials for monitoring DA in the prior art, and adopts a method of preparing In through vacancy engineering and interface design strategy. 2 S 3-x Se x@NC composite heterogeneous nanomaterials method not only produces a uniform heterojunction interface, but also because some S atoms are replaced by Se atoms, anion vacancies are generated in situ, so that this defect-enriched microstructure obtains the advantages of uniform heterojunction interface, expanded interlayer distance and special S-In-Se bonds. In the technical research and development stage, after determining the framework research and development direction of vacancy engineering, the inventors found that if the introduction of Se elements by unreasonable methods will not only not cause vacancies, but also cause the collapse of the material, resulting in a significant reduction in electrochemical performance. The present invention introduces a nitrogen-doped carbon layer before the introduction of Se elements, which not only maintains the stability of the material structure, but also increases the conductivity of the material. It is ensured that when the Se element is introduced, the integrity of the material can be guaranteed while generating a large number of vacancies. Moreover, in view of the current research status, the application of p-zone metals and p-zone metal compounds in the field of electrochemical sensing is relatively rare. This technical solution adopts heterojunction interface design, heteroatom doping and vacancy regulation strategies to synthesize In. 2 S 3–x Se x @NC composite heterogeneous nanomaterials and realize their application in the field of electrochemical sensing.

[0031] This technical solution provides 2 S 3–x Se x @NC composite heterogeneous nanomaterials have the following main characteristics:

[0032] 1. Composition characteristics: In 2 S 3-x Se x The presence of low electronegativity anions in the carbon layer can increase the electron density around the metal catalytic active center (In); in addition, the nitrogen-doped carbon layer has high electronic conductivity, and this composition optimizes the electrochemical reaction steps of bioactive molecules;

[0033] 2. Defective process and precise doping: In 2 S 3 The Se element is introduced into the molten metal. This doping method can produce abundant vacancies and adjust the original In 2 S 3 The electronic configuration of 2 S 3-x Se x It has a high ion / electron transfer rate and a heterogeneous interface that is conducive to the electrochemical oxidation of DA; in addition, this technical solution uses In-MOFs materials as a template, which can guide the formation of heterogeneous structural materials with different structures and has a wide range of applicability;

[0034] 3. Structural advantages: The uniform heterojunction interface and layered structure can fully expose the reaction active sites, shorten the analyte / electrolyte diffusion path, and reduce the volume deformation during the continuous electrochemical reaction.

[0035] Therefore, when the present invention is used for the detection of biologically active molecules, it shows high sensitivity, low detection limit, excellent anti-interference performance, good stability, repeatability and reproducibility. When used for the detection of actual samples, it shows high accuracy and reliability. This study emphasizes the novel method of creating anion vacancies and uniform heterojunction interfaces, provides feasible suggestions for the logical design and construction of efficient sensing platforms or extensive catalytic materials, and further fills the gap of p-region metal disulfides in the construction of high-performance sensing platforms. The programmed synthesis steps of the present invention will provide a new perspective for the design of ternary metal sulfide compounds, which is a more convenient and efficient strategy, expanding the application of p-region metals in sensing and even biology, clinical medicine and other fields.

[0036] In addition, the In 2 S 3–x Se x @NC composite heterogeneous nanomaterials do not require expensive biological templates and will not cause In 2 S 3–x Se x @NC composite heterogeneous nanomaterial aggregation can prepare In with different microstructures by changing the structure of precursor In-MOFs 2 S 3–x Se x @NC nanomaterials have low-cost synthetic raw materials, simple processes, low energy consumption, and easy-to-achieve reaction conditions. The synthesis process is simple and controllable, which ensures the success rate of material synthesis. It can be mass-produced and can guide the synthesis of more ternary metal sulfide compounds, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The scanning electron microscope images of the spindle-shaped In-MOFs and In2S3–xSex@NC composite heterogeneous nanomaterials prepared in the present invention. a and b are In-MOFs, c and d are In 2 S 3–x Se x @NC.

[0038] Figure 2 Transmission electron microscopy images of the spindle-shaped In-MOFs and In2S3–xSex@NC composite heterogeneous nanomaterials prepared in the present invention. a and b are In-MOFs, c and d are In 2 S 3–x Se x @NC.

[0039] Figure 3 In prepared by the present invention 2 S 3–x Se x @X-ray diffraction and electron paramagnetic resonance spectra of NC composite heterogeneous nanomaterials.

[0040] Figure 4 In prepared by the present invention 2 S 3–x Se x @X-ray photoelectron spectrum of NC composite heterogeneous nanomaterials.

[0041] Figure 5 In prepared by the present invention 2 S 3–x Se x @NC composite heterogeneous nanomaterials cyclic voltammetry (CV) scans in DA solutions of different concentrations and CV curves at different scan rates in 1.5 mM DA solution.

[0042] Figure 6 In prepared by the present invention 2 S 3–x Se x @Chronoamperometric curve of NC composite heterogeneous nanomaterials.

[0043] Figure 7 In prepared by the present invention 2 S 3–x Se x @NC Anti-interference performance diagram of composite heterogeneous nanomaterials.

[0044] Figure 8 In prepared by the present invention 2 S 3–x Se x @NC Long-term stability and repeatability diagrams of composite heterogeneous nanomaterials.

[0045] Fig. 9 Comparative Example 1In of the present invention 2 S 3–x Se x Performance test results of composite heterogeneous nanomaterials. a is a scanning electron microscope image, b is a transmission electron microscope image, and c is a CV scan of the material in DA solutions of different concentrations.

[0046] Fig.10 Comparative Example 2In of the present invention 2 S 3 @NC composite heterogeneous nanomaterial performance test results. a is a scanning electron microscope image, b is a transmission electron microscope image, and c is a CV scan of the material in DA solutions of different concentrations.

[0047] Fig.11 Comparative Example 3In of the present invention 2 Se 3 @NC composite heterogeneous nanomaterial performance test results. a is a scanning electron microscope image, b is a transmission electron microscope image, and c is a CV scan of the material in DA solutions of different concentrations. DETAILED DESCRIPTION

[0048] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0049] Example 1

[0050] A composite heterogeneous nanomaterial having abundant ion defects and a uniform heterogeneous interface, wherein the anion defects are partially replaced by Se elements to form In 2 S 3 The uniform heterogeneous interface is created by the S element in the polydopamine-derived nitrogen-doped carbon layer and the In 2 S 3–x Se x The precursor of the constructed nanomaterial is In-MOFs, and composite heterogeneous nanomaterials with different structures can be derived by changing the structure of the precursor In-MOFs.

[0051] A method for preparing a composite heterogeneous nanomaterial comprises the following steps:

[0052] Step 1: Preparation of precursor In-MOFs: Indium(III) nitrate hydrate (In(NO 3 ) 3 ·5H 2 O, 0.5 g) was added to 60 mL N, N-dimethylformamide (DMF) and stirred continuously to dissolve. Subsequently, 1,4-phthalic acid (PTA, 1 g) and 1,2-benzisothiazolin-3-1 (BIT, 0.5 g) were added to the above solution and stirred for 30 min. After heating at 100 ° C for 4 hours in a 100 mL stainless steel autoclave, the harvested white precipitate was centrifuged and washed several times with DMF and deionized water, and finally freeze-dried to obtain the white spindle-shaped precursor In-MOFs.

[0053] Step 2, preparation of the intermediate product In-MOFs@PDA: 200 mg In-MOFs and 100 mg dopamine powder obtained in step 1 were added to 100 mL Tris buffer solution (10 mM) and vigorously stirred at room temperature for 10 hours. It was observed that the In-MOFs gradually changed from white to black, that is, the self-polymerization process was completed, and then the black product was filtered and washed to obtain the spindle-shaped intermediate product In-MOFs@PDA.

[0054] Step 3: Place 100 mg In-MOFs@PDA and 500 mg sulfur powder obtained in step 2 in two small porcelain boats, and then place the two small porcelain boats at both ends of a larger covered porcelain boat. -1 The reaction was continued at 500 °C for 2 h in an argon flow for sulfurization and carbonization. Finally, a black sample was obtained after a natural cooling process, and a spindle-shaped intermediate product In was obtained. 2 S 3 @NC.

[0055] Step 4: In obtained in step 3 2 S 3 @NC and selenium powder, in a ratio of 1:4, were placed on both sides of the porcelain boat and covered with a lid. At a heating rate of 2 °C min -1 The reaction was continued at 400 °C for 2 h in an argon flow for selenization. Finally, a black sample was obtained after a natural cooling process, and the spindle-shaped final product In was obtained. 2 S 3–x Se x @NC.

[0056] Example 2

[0057] A method for preparing a composite heterogeneous nanomaterial comprises the following steps:

[0058] Step 1: Preparation of precursor In-MOFs: Indium(III) nitrate hydrate (In(NO 3 ) 3 ·5H 2 O, 0.15g) and 1,3,5-benzenetricarboxylic acid (H 3 BTC, 0.75 g) was added to a mixed solution of N, N-dimethylformamide (48 mL) and methanol solution (12 mL). After the powder was dissolved, the transparent mixture was transferred to a 100 mL stainless steel high-pressure reactor. The reactor was sealed and heated to 120 ° C for 24 h. The resulting precipitate was centrifuged and washed several times with methanol, and finally vacuum dried overnight to obtain white flake precursor In-MOFs.

[0059] Step 2, preparation of the intermediate product In-MOFs@PDA: 200 mg In-MOFs and 100 mg dopamine powder obtained in step 1 were added to 100 mL Tris buffer solution (10 mM) and vigorously stirred at room temperature for 10 hours. It was observed that the In-MOFs gradually changed from white to black, that is, the self-polymerization process was completed, and then the black product was filtered and washed to obtain the intermediate product In-MOFs@PDA in the form of flakes.

[0060] Step 3: Place 100 mg In-MOFs@PDA and 500 mg sulfur powder obtained in step 2 in two small porcelain boats, and then place the two small porcelain boats at both ends of a larger covered porcelain boat. -1 The reaction was continued at 500 °C for 2 h in an argon flow for sulfurization and carbonization. Finally, a black sample was obtained after a natural cooling process, and a thin flake intermediate product In was obtained. 2 S 3 @NC.

[0061] Step 4: In obtained in step 3 2 S 3 @NC and selenium powder, in a ratio of 1:4, were placed on both sides of the porcelain boat and covered with a lid. At a heating rate of 2 °C min -1 The reaction was continued at 400 °C for 2 h in an argon flow for selenization. Finally, a black sample was obtained after a natural cooling process, and the final product In was obtained in the form of a thin sheet. 2 S 3–x Se x @NC.

[0062] Example 3

[0063] A method for preparing a composite heterogeneous nanomaterial comprises the following steps:

[0064] Step 1: Preparation of precursor In-MOFs: Indium(III) nitrate hydrate (In(NO 3 ) 3 6H 2 O, 0.82g) and 1,4-phthalic acid (H 3 BDC, 0.33 g) was added to N, N-dimethylformamide (20 mL) solution. Then, sodium acetate aqueous solution (100 mL, 1 M) was added under vigorous stirring. The resulting reaction mixture was placed in a 400 ° C oil bath for 30 min, and the resulting precipitate was centrifuged, washed with distilled water and anhydrous ethanol for multiple times, and vacuum dried at 60 ° C for 5 h to obtain white rod-shaped precursor In-MOFs.

[0065] Step 2, preparation of the intermediate product In-MOFs@PDA: 200 mg In-MOFs and 100 mg dopamine powder obtained in step 1 were added to 100 mL Tris buffer solution (10 mM) and vigorously stirred at room temperature for 10 hours. It was observed that In-MOFs gradually changed from white to black, that is, the self-polymerization process was completed, and then the black product was filtered and washed to obtain the rod-shaped intermediate product In-MOFs@PDA.

[0066] Step 3: Place 100 mg In-MOFs@PDA and 500 mg sulfur powder obtained in step 2 in two small porcelain boats, and then place the two small porcelain boats at both ends of a larger covered porcelain boat. -1 The reaction was continued at 500 °C for 2 h in an argon flow for sulfurization and carbonization. Finally, a black sample was obtained after a natural cooling process, and the rod-shaped intermediate product In 2 S 3 @NC.

[0067] Step 4: In obtained in step 3 2 S 3 @NC and selenium powder, in a ratio of 1:4, were placed on both sides of the porcelain boat and covered with a lid. At a heating rate of 2 °C min -1 The reaction was continued at 400 °C for 2 h in an argon flow for selenization. Finally, a black sample was obtained after a natural cooling process, and the rod-shaped final product In 2 S 3–x Se x @NC.

[0068] Example 4

[0069] A method for preparing a composite heterogeneous nanomaterial comprises the following steps:

[0070] Step 1: Preparation of precursor In-MOFs: Indium(III) nitrate hydrate (In(NO 3 ) 3 ·5H 2 O, 0.5g) was added to 60mL N,N-dimethylformamide (DMF) and stirred continuously to dissolve. Subsequently, 1,4-phthalic acid (PTA, 1g) and 1,2-benzisothiazolin-3-1 (BIT, 0.5g) were added to the above solution and stirred for 30min. After heating at 100℃ for 4 hours in a 100mL stainless steel autoclave, the harvested white precipitate was centrifuged and washed several times with DMF and deionized water, and finally freeze-dried. The white spindle-shaped precursor In-MOFs was obtained.

[0071] Step 2, preparation of the intermediate product In-MOFs@PDA: 400 mg In-MOFs and 100 mg dopamine powder obtained in step 1 were added to 100 mL Tris buffer solution (10 mM) and vigorously stirred at room temperature for 10 hours. It was observed that the In-MOFs gradually changed from white to black, that is, the self-polymerization process was completed, and then the black product was filtered and washed to obtain the spindle-shaped intermediate product In-MOFs@PDA.

[0072] Step 3: Place 100 mg In-MOFs@PDA and 500 mg sulfur powder obtained in step 2 in two small porcelain boats, and then place the two small porcelain boats at both ends of a larger covered porcelain boat. -1 The reaction was continued at 500 °C for 2 h in an argon flow for sulfurization and carbonization. Finally, a black sample was obtained after a natural cooling process, and a spindle-shaped intermediate product In was obtained. 2 S 3 @NC.

[0073] Step 4: In obtained in step 3 2 S 3 @NC and selenium powder, in a ratio of 1:4, were placed on both sides of the porcelain boat and covered with a lid. At a heating rate of 2 °C min -1 The reaction was continued at 400 °C for 2 h in an argon flow for selenization. Finally, a black sample was obtained after a natural cooling process, and the spindle-shaped final product In was obtained. 2 S 3–x Se x @NC.

[0074] Comparative Example 1

[0075] This comparative example 2 S 3–x Se x The method for preparing a composite heterogeneous nanomaterial comprises the following steps:

[0076] Step 1: Indium(III) nitrate hydrate (In(NO 3 ) 3 ·5H 2 O, 0.5 g) was added to 60 mL N, N-dimethylformamide (DMF) and stirred continuously to dissolve. Subsequently, 1,4-phthalic acid (PTA, 1 g) and 1,2-benzisothiazolin-3-1 (BIT, 0.5 g) were added to the above solution and stirred for 30 min. After heating at 100 ° C for 4 hours in a 100 mL stainless steel autoclave, the harvested white precipitate was centrifuged and washed several times with DMF and deionized water, and finally freeze-dried to obtain the white spindle-shaped precursor In-MOFs.

[0077] Step 2: Place 100 mg of In-MOFs and 500 mg of sulfur powder obtained in step 1 in two small porcelain boats, and then place the two small porcelain boats at both ends of a larger covered porcelain boat. -1 The reaction was continued at 500 °C for 2 h in an argon flow for sulfurization and carbonization. Finally, a black sample was obtained after a natural cooling process, and a spindle-shaped intermediate product In was obtained. 2 S 3 .

[0078] Step 3: In obtained in step 2 2 S 3 and selenium powder in a ratio of 1:4, placed on both sides of the porcelain boat and covered with a lid. -1 The reaction was continued at 400°C for 2 h in an argon flow for selenization. Finally, a black sample was obtained after a natural cooling process, and the spindle-shaped comparative product In of Example 1 was obtained. 2 S 3–x Se x .

[0079] Comparative Example 2

[0080] This comparative example 2 S 3 The preparation method of @NC composite heterogeneous nanomaterials comprises the following steps:

[0081] Step 1: Indium(III) nitrate hydrate (In(NO 3 ) 3 ·5H 2 O, 0.5g) was added to 60mL N,N-dimethylformamide (DMF) and stirred continuously to dissolve. Subsequently, 1,4-phthalic acid (PTA, 1g) and 1,2-benzisothiazolin-3-1 (BIT, 0.5g) were added to the above solution and stirred for 30min. After heating at 100℃ for 4 hours in a 100mL stainless steel autoclave, the harvested white precipitate was centrifuged and washed several times with DMF and deionized water, and finally freeze-dried. The white spindle-shaped precursor In-MOFs was obtained.

[0082] Step 2: Add 200 mg of In-MOFs and 100 mg of dopamine powder obtained in step 1 to 100 mL of Tris buffer solution (10 mM) and stir vigorously at room temperature for 10 hours. It is observed that the In-MOFs gradually change from white to black, that is, the self-polymerization process is completed, and then the black product is filtered and washed. The spindle-shaped intermediate product In-MOFs@PDA can be obtained.

[0083] Step 3: Place 100 mg In-MOFs@PDA and 500 mg sulfur powder obtained in step 2 in two small porcelain boats, and then place the two small porcelain boats at both ends of a larger covered porcelain boat. -1 In an argon flow, the reaction was continued at 500 ° C for 2 hours for sulfurization and carbonization. Finally, a black sample was obtained after a natural cooling process. The spindle-shaped comparison product In 2 S 3 @NC.

[0084] Comparative Example 3

[0085] This comparative example 2 Se 3 The preparation method of @NC composite heterogeneous nanomaterials comprises the following steps:

[0086] Step 1: Indium(III) nitrate hydrate (In(NO 3 ) 3 ·5H 2 O, 0.5g) was added to 60mL N,N-dimethylformamide (DMF) and stirred continuously to dissolve. Subsequently, 1,4-phthalic acid (PTA, 1g) and 1,2-benzisothiazolin-3-1 (BIT, 0.5g) were added to the above solution and stirred for 30min. After heating at 100℃ for 4 hours in a 100mL stainless steel autoclave, the harvested white precipitate was centrifuged and washed several times with DMF and deionized water, and finally freeze-dried. The white spindle-shaped precursor In-MOFs was obtained.

[0087] Step 2: Add 200 mg of In-MOFs and 100 mg of dopamine powder obtained in step 1 to 100 mL of Tris buffer solution (10 mM) and stir vigorously at room temperature for 10 hours. It is observed that the In-MOFs gradually change from white to black, that is, the self-polymerization process is completed, and then the black product is filtered and washed. The spindle-shaped intermediate product In-MOFs@PDA can be obtained.

[0088] Step 3: Place the In-MOFs@PDA@NC and selenium powder obtained in step 2 at a ratio of 1:4 on both sides of the porcelain boat and cover it with a lid. -1 The reaction was continued for 2 h at 500 °C in an argon flow for selenization and carbonization. Finally, a black sample was obtained after a natural cooling process. The spindle-shaped comparison product In 2 Se 3 @NC.

[0089] Experimental Example Performance Test

[0090] 1. The hammer-shaped In-MOFs precursor prepared in Example 1 and In 2 S 3–x Se x The morphology of @NC composite heterogeneous nanomaterials was observed by field emission scanning microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM). Figure 1 and Figure 2 shown.

[0091] from Figure 1 a and Figure 1 b It can be seen that the In-MOFs precursor presents a spindle-shaped structure with a width range of 500-1000nm and a smooth outer surface, which is very conducive to the deposition of the polydopamine layer. Subsequently, a high-temperature sulfurization and selenization process was used to obtain the hollow In 2 S 3–x Se x @NC, looks like Figure 1 c and Figure 1 d. At this time, a small amount of particles appeared in the material and attached to the spindle In 2 S 3–x Se x @NC surface, and its size becomes smaller due to shrinkage under high temperature conditions. Figure 2 a and Figure 2 b It can be seen that the spindle-shaped In-MOFs precursor is solid. The high-temperature selenization and sulfurization process not only does not destroy the original spindle configuration, but also makes the final In 2 S 3–x Se x @NC composite heterogeneous nanomaterials present a hollow structure. Figure 2 c and Figure 2 As shown in d.

[0092] 2. The In prepared in Example 1 2 S 3–x Se x The @NC composite heterogeneous nanomaterials were subjected to X-ray diffraction (XRD), electron paramagnetic resonance (EPR) and X-ray photoelectron analysis (XPS), and the results are as follows Figure 3 and Figure 4 shown.

[0093] from Figure 3 From the XRD spectrum of a, it can be seen that In 2 S 3–x Se x Diffraction peaks of @NC composite heterogeneous nanomaterials and β-In 2 S 3The peaks at 27.4°, 33.2°, 43.6° and 47.6° belong to β-In 2 S 3 (213), (220), (323) and (2212) faces. However, due to In 2 S 3 The unit cell expands with the addition of large-sized Se, In 2 S 3–x Se x Peak potential of @NC composite heterogeneous nanomaterials relative to β-In 2 S 3 The standard card of 2000 is slightly shifted to lower degrees. This also suggests the mixing of Se and S atoms and the formation of Se-In-S bonds. Figure 3 The EPR spectrum of b shows that In 2 S 3–x Se x @NC composite heterogeneous nanomaterials have a typical symmetrical Lorentz line, and its g-factor signal is located at 2.004, and the intensity is also relatively large, which shows that In 2 S 3–x Se x Abundant defects in @NC composite heterogeneous nanomaterials can be attributed to the incorporation of Se into In 2 S 3 Anion vacancies are generated during the crystallization process. Figure 4 XPS shows that the composite heterogeneous nanomaterial is mainly composed of four elements: In, S, Se, C and N, and the high-resolution spectra of In3d, S2p, Se3p and Se3d are analyzed. The high-resolution spectra show that the binding energies of different peaks are consistent with the different electronic valence states and bond energies of the elements in the material, thus proving that the In-based 2 S 3–x Se x The composition and elemental valence of @NC composite heterogeneous nanomaterials, as well as the strong bond coupling between In and Se / S and the increase in defect sites, are both beneficial to improving the electrochemical sensing performance.

[0094] 3. Take the In prepared in Example 1 2 S 3–x Se x2.5 mg of @NC composite heterogeneous nanomaterials were dissolved in 1 mL of deionized water to form a uniform suspension, which was then coated on a clean glassy carbon electrode with a diameter of 3 mm. The electrode was then dried at room temperature to obtain the working electrode required for the electrochemical sensing test. A platinum wire was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode to form a standard three-electrode system (the same below). The electrolyte used was 0.01 M phosphate buffer solution (PBS), and the voltage range was -0.3 to 0.4 V. 2 S 3–x Se x Electrocatalytic performance of @NC composite heterogeneous nanomaterials towards DA active molecules.

[0095] Figure 5 a is the cyclic voltammetry (CV) curve of the three-electrode system in DA solutions of different concentrations (0mM to 1.1mM) at a scan rate of 50mV / s. It can be observed from the figure that different curves have obvious redox peaks, indicating that effective electrochemical oxidation reactions have occurred in DA molecules, and the peak current value increases with the increase of DA concentration, indicating that this In 2 S 3–x Se x @NC composite heterogeneous nanomaterials have the ability to quantitatively detect DA molecules. Figure 5 b is the CV curve of the three-electrode system in a PBS solution containing 0.5 mM DA at different scan rates (5 mV / s to 150 mV / s). As can be seen from the figure, as the scan rate increases, the curve shape remains good, but the oxidation peak and reduction peak current increase with the increase in the scan rate, and the peak current value is linearly related to the square root of the scan rate, which shows that In 2 S 3–x Se x The kinetic process of DA molecule detection by @NC composite heterogeneous nanomaterials is a diffusion-controlled process. At the same time, the oxidation peak potential does not change, and the reduction peak potential moves slightly to the negative direction, indicating that the conversion between DA and its oxidation product dopamine quinone (DAQ) is reversible.

[0096] 4. The In prepared in Example 1 2 S 3–x Se x The three-electrode system constructed by @NC composite heterogeneous nanomaterials was used to measure the chronoamperometric curve of the continuous addition of different concentrations of hydrogen peroxide at a working potential of 0.30 V to calculate In 2 S 3–x Se x @NC composite heterogeneous nanomaterials for the sensitivity, detection limit and detection range of hydrogen peroxide detection.

[0097] like Figure 6As shown in the figure, with the addition of DA solutions of different concentrations, different responses with different increase amplitudes were generated and increased in a step-like manner. The material responded quickly and significantly to DA, reaching a steady-state current density of 96% within 5 seconds, which reflects the rapid adsorption and effective oxidation of DA on the surface of In2S3–xSex@NC composite heterogeneous nanomaterials. The relationship between current and DA concentration was plotted and linearly fitted, indicating that its sensitivity in the concentration range of 0 to 500 nM was 207.12 μAμM -1 cm -2 The detection limit is 0.87 nM. When compared with the reported DA electrochemical sensors based on In, its detection limit and sensitivity are incomparable.

[0098] 5. The In prepared in Example 1 2 S 3–x Se x The three-electrode system constructed by @NC composite heterogeneous nanomaterials was used to measure the chronoamperometric curves of DA and different types of interfering substances under the working potential of 0.30V to evaluate the In 2 S 3–x Se x @NC composite heterogeneous nanomaterials' selectivity and anti-interference ability for DA detection.

[0099] The results are as follows Figure 7 As shown in the figure, the addition of DA produces a rapid and significant increase in the response current, while the addition of interfering substances can only detect a slight current change, which can be ignored, indicating the excellent selectivity of the material. By comparing the current response of hydrogen peroxide before and after the addition of interfering substances, the change is not large, indicating that In 2 S 3–x Se x @NC composite heterogeneous nanomaterials still have a strong recognition ability for DA, confirming the anti-interference ability of the synthesis.

[0100] 6. The In prepared in Example 1 2 S 3–x Se x @NC The three-electrode system constructed by composite heterogeneous nanomaterials uses one working electrode to perform ten repeated DPV measurements on 10μM DA to evaluate the repeatability of composite heterogeneous nanomaterials for DA detection. One working electrode is used to measure the DPV current response to DA once a day for ten consecutive days to evaluate the long-term stability of composite heterogeneous nanomaterials for DA detection.

[0101] like Figure 8 As shown in a, after 10 days of testing, its initial signal can still maintain about 92.4%; Figure 8As shown in b, by counting ten DPV scan responses to 10 μM DA, the relative standard deviation (RSD) value of the sensor electrode was calculated to be less than 1.0%. 2 S 3–x Se x @NC composite heterogeneous nanomaterials have good repeatability and excellent long-term stability for DA molecule detection.

[0102] It should be noted that the In prepared in Examples 2 to 4 2 S 3–x Se x The performance verification of @NC composite heterogeneous nanomaterials is the same as in Example 1, and can be used to construct different electrochemical detection platforms, which are not listed here one by one.

[0103] 7. Comparative Example Performance Test: The composite heterogeneous nanomaterials prepared in Comparative Examples 1 to 3 were observed for their morphology using a field emission scanning microscope (FESEM) and a high resolution transmission electron microscope (HRTEM). Figures 9-11 As shown: In each figure, a is a scanning electron microscope image, and b is a transmission electron microscope image.

[0104] 2.5 mg of the composite heterogeneous nanomaterials prepared in Comparative Examples 1 to 3 were dissolved in 1 mL of deionized water to form a uniform suspension, which was then coated on a clean glassy carbon electrode with a diameter of 3 mm, and the electrode was dried at room temperature to obtain the working electrode required for the electrochemical sensing test. A platinum wire was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode to form a standard three-electrode system (the same below). The electrolyte used was 0.01 M phosphate buffer solution (PBS), and the voltage range was -0.3 to 0.4 V. The electrocatalytic performance of the composite heterogeneous nanomaterials in each comparative example on DA active molecules was explored, and the results were as follows: Figures 9-11 As shown in c.

[0105] The above results show that: 2 S 3–x Se x @NC intermediate product of heterogeneous nanomaterials 2 S 3 @NC composite heterogeneous nanomaterials ( Fig.10 ). This nanomaterial does not undergo the selenization process, which means that the Se element does not replace the S element, resulting in In 2 S 3 @NC composite heterogeneous nanomaterial defects reduction. From the CV graph of DA molecule detection, the reduction of defects and the lack of Se element lead to the decline of its electrochemical detection performance. Indium without nitrogen-doped carbon layer protective layer was prepared. 2 S 3-x Se x ( Fig. 9), which shows the same 2 S 3-x Se x @NC, and some aggregated nanoparticles were found in the SEM image, which means that the introduction of nitrogen-doped carbon layer promotes In 2 S 3-x Se x @NC realizes a stable hollow structure. The CV graph of DA molecule detection shows that the presence of nitrogen-doped carbon layer can not only enhance the long-term stability of the material during electrochemical detection, but also increase its conductivity, resulting in In 2 S 3–x Se x The electrochemical oxidation of DA in the@NC composite heterogeneous nanomaterials was fast and efficient. 2 Se 3 @NC composite heterogeneous nanomaterials ( Fig.11 ). Since the synthesis of this control sample did not involve the sulfurization process, the hollow structure was not complete, but only had a partial hollow cavity. The formation of a hollow structure would increase the electrochemical reaction sites of active molecules and accelerate the electron transfer rate, while the generation of a partial hollow cavity would significantly reduce its electrochemical performance for DA molecule detection.

[0106] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A composite heterogeneous nanomaterial, characterized in that: The nanomaterial uses In-MOFs as a precursor and constructs anion defects and a uniform heterogeneous interface. The anion defects are created by partially replacing the S element in In2S3 with Se elements. The uniform heterogeneous interface exists between the nitrogen-doped carbon layer derived from polydopamine and the In2S 3–x Se x between.

2. The composite heterogeneous nanomaterial according to claim 1, characterized in that: The morphology of the In-MOFs precursor is spindle-shaped, flake-shaped or rod-shaped.

3. A composite heterogeneous nanomaterial according to claim 2, characterized in that: The preparation method of In-MOFs spindle morphology comprises the following steps: S1. dissolving a precursor containing an indium source in N,N-dimethylformamide and stirring continuously; S2, adding 1,4-phthalic acid and 1,2-benzisothiazolin-3-one to the above solution in sequence, and stirring to mix evenly; S3, transferring the mixture into an autoclave, heating and reacting to obtain a white precipitate; S4. The white precipitate was centrifuged, washed with DMF and deionized water for multiple times, and freeze-dried to obtain white spindle-shaped In-MOFs.

4. The composite heterogeneous nanomaterial according to claim 2, characterized in that: The method for preparing In-MOFs flake morphology comprises the following steps: S1, adding a precursor containing an indium source and 1,3,5-benzenetricarboxylic acid to a mixed solution of N,N-dimethylformamide and a methanol solution; S2. After the powder is dissolved, the transparent mixture is transferred to a high-pressure reactor, sealed and heated for reaction; S3. The obtained precipitate was centrifuged and washed with methanol several times, and then vacuum dried overnight to obtain white flaky In-MOFs.

5. The composite heterogeneous nanomaterial according to claim 2, characterized in that: The preparation method of In-MOFs rod-like morphology comprises the following steps: S1, adding a precursor containing an indium source and 1,4-benzenedicarboxylic acid to N,N-dimethylformamide, and then adding a sodium acetate aqueous solution under vigorous stirring; S2, placing the obtained reaction mixture in an oil bath for reaction to obtain a precipitate; S3. The obtained precipitate was centrifuged, washed with distilled water and anhydrous ethanol several times, and then vacuum dried to obtain white rod-shaped In-MOFs.

6. A composite heterogeneous nanomaterial according to any one of claims 3 to 5, characterized in that: The precursor of the indium source is at least one of hydrated indium nitrate (In(NO3)3·4H2O, In(NO3)3·5H2O, In(NO3)3·6H2O).

7. The method for preparing a composite heterogeneous nanomaterial according to claim 6, characterized in that: The steps include: Step 1: Add dopamine and In-MOFs powder into a buffer solution and stir at room temperature. When the white In-MOFs turns black, the self-polymerization process is completed. Then filter and wash to obtain the In-MOFs@PDA intermediate. Step 2: In-MOFs@PDA and sulfur powder are placed in a porcelain boat, and subjected to high-temperature carbonization and sulfurization treatment in a protective atmosphere. After the reaction is completed, the mixture is cooled to obtain a black sample In2S3@NC. Step 3: Place In2S3@NC and tin powder at both ends of a porcelain boat, perform high-temperature selenization treatment in a protective atmosphere, and cool down after the reaction to obtain the final product In2S 3–x Se x @NC.

8. The method for preparing a composite heterogeneous nanomaterial according to claim 7, characterized in that: In step 1, the mass ratio of dopamine to In-MOFs powder is 1:1 to 1:4, the buffer solution is Tris solution, the concentration of the buffer solution is 5 to 20 mM, and the stirring time is 6 to 14 hours.

9. The method for preparing a composite heterogeneous nanomaterial according to claim 8, characterized in that: In step 2, the mass ratio of In-MOFs@PDA and sulfur powder is 1:2~1:10, and the high-temperature carbonization and sulfurization reactions are heated to 400~800°C at a heating rate of 1~10°C / min, and the reaction time is 1~5h; in step 3, the mass ratio of In2S3@NC and tin powder is 1:1~1:4, and the high-temperature selenization reaction is heated to 300~700°C at a heating rate of 1~10°C / min, and the reaction time is 1~5h.

10. Use of the composite heterogeneous nanomaterial according to claim 6 in detecting dopamine molecules.